(untitled) (Jurnal Teknologi (Sciences & Engineering), 2025)
An accurate estimation of wave overtopping discharge on rock revetment is important to protect coastal areas from possible hazards. The mean discharge value is often used in the coastal structural design. However, the anticipated impact of the maximum volume of overtopping by individual waves is expected to be significant in wave overtopping analysis. This research investigates the mean discharge of wave overtopping and maximum volume of overtopping by individual wave using two-dimensional (2D) physical model tests. The rock revetment model consists of armour layer with D50=46 mm, a filter layer with D50=13 mm, and an impermeable core, with a thickness of 2D50 for armour and filter layers. Wave overtopping volumes obtained from physical tests were then compared to EurOtop empirical formulae. The results showed that the variability of wave overtopping increases when the wave height and water level increase. This variation falls within the specified interval boundaries by EurOtop empirical methods, with the exception of the lower maximum volume of overtopping by individual waves. Furthermore, the findings indicate that the maximum volume of overtopping by individual waves can exceed the mean wave overtopping volume by up to 85%.